PENGARUH AGRESIVITAS PAJAK DAN UKURAN PERUSAHAAN TERHADAP UTANG JANGKA PENDEK (STUDI EMPIRIS PADA PERUSAHAAN YANG TERDAFTAR DI LQ45 TAHUN 2015 – 2017) - Luthfiyyah Azhari Rachman; Andrian Budi Prasetyo (Diponegoro Journal of Accounting, 2019)
This study investigates the association between tax aggressiveness, firm size and maturity structure of debt. The independent variables are tax aggressiveness and firm size. Short Term Debt is the dependent variable of this study, to reflect the maturity structures of debt. The result shows that corporate tax aggressiveness has a positive and significant effect to Short Term Debt, while firm size has a negative and significant effect to Short Term Debt in companies that are listed in LQ 45 stock index between 2015 – 2017.